2017
DOI: 10.1111/mve.12254
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley fever virus and European mosquitoes: vector competence of Culex pipiens and Stegomyia albopicta (= Aedes albopictus)

Abstract: Abstract. Rift Valley fever (RVF) is a mosquito-borne disease caused by the RiftValley fever virus (RVFV). Rift Valley fever affects a large number of species, including human, and has severe impact on public health and the economy, especially in African countries. The present study examined the vector competence of three different European mosquito species, Culex pipiens (Linnaeus, 1758) form molestus (Diptera: Culicidae), Culex pipiens hybrid form and Stegomyia albopicta (= Aedes albopictus) (Skuse, 1894) (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 60 publications
3
64
0
Order By: Relevance
“…Studies have shown that RVFV epidemics typically follow periods of heavy rainfall conducive to large mosquito populations (Davies, Linthicum, & James, 1985;Hassan, Ahlm, Sang, & Evander, 2011;Leedale, Jones, Caminade, & Morse, 2016;Redding, Tiedt, Lo Iacono, Bett, & Jones, 2017) as well as the trade and importation of infected animals into susceptible regions (Napp et al, 2018). In Africa, RVFV is mainly transmitted by the Aedes aegypti mosquito, however, a growing number of studies have made it clear that other mosquito species present in Asia, Europe and North/South America are experimentally competent as RVFV vectors (Brustolin et al, 2017;Ndiaye et al, 2016;Turell et al, 2015). Therefore, if RVFV were to be introduced into other continents and their endemic mosquito populations, it could cause widespread epidemics and could seriously impact the health of human populations and economically important livestock herds.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that RVFV epidemics typically follow periods of heavy rainfall conducive to large mosquito populations (Davies, Linthicum, & James, 1985;Hassan, Ahlm, Sang, & Evander, 2011;Leedale, Jones, Caminade, & Morse, 2016;Redding, Tiedt, Lo Iacono, Bett, & Jones, 2017) as well as the trade and importation of infected animals into susceptible regions (Napp et al, 2018). In Africa, RVFV is mainly transmitted by the Aedes aegypti mosquito, however, a growing number of studies have made it clear that other mosquito species present in Asia, Europe and North/South America are experimentally competent as RVFV vectors (Brustolin et al, 2017;Ndiaye et al, 2016;Turell et al, 2015). Therefore, if RVFV were to be introduced into other continents and their endemic mosquito populations, it could cause widespread epidemics and could seriously impact the health of human populations and economically important livestock herds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, serological studies have suggested that RVFV may be circulating in Turkey (71) and Iran (72). To date there has been no evidence of RVFV introduction into Europe, although some researchers have speculated that this is likely based on previous examples of translocation out of Africa and a number of studies have shown that mosquito species in Europe are competent vectors for the virus (12,73). With the possible exception of human travel from Africa, it seems unlikely that RVFV could be introduced inadvertently in livestock or livestock products to the UK due to paucity of such trade at the current time.…”
Section: Rift Valley Fevermentioning
confidence: 99%
“…In terms of vector competence, European Cx. pipiens hybrid forms have been shown to be able to transmit WNV [101] and RVFV [102].…”
Section: Culex Pipiens Biotype Molestus Forskal 1775mentioning
confidence: 99%
“…Ae. albopictus is a competent vector to 26 arboviruses in laboratory conditions [125] including WNV [101] and RVFV [102]. It has also been found infected with USUV in the field [126].…”
Section: Aedes (Stegomyia) Albopictus (Skuse1895)mentioning
confidence: 99%